Good Corporate Governance on Earnings Management - Aulia Claraning Sukmawati (YUME : Journal of Management, 2021)
This study aims to analyze the effect of corporate governance, company performance, and firm characteristics on earning management. The data used in the research are secondary data, namely financial statements of non financial companies listed on Indonesian Stock Exchange in period 2010-2018 with a total sampel of 116 companies. Corporate governance is proxied by managerial ownership, institusional ownership, ownership concentration, board size, and board activity. Company performance is proxied by leverage risk and sales growth. And firm characteristics as a control variable proxied by age, and size. This study analyzed using linier regression analysis that is ordinary least square (OLS). The result of the study indicate that institusional ownership, ownership concentration, and size has a negatif significant effect on earning management. Then board size and age variable has a positive significant effect on earning management. And then managerial ownership, board activity, leverage risk, and sales growth has no significant effect on earning management.